Approximate convex decomposition and transfer for animated meshes - Thul, Daniel; Ladický, Ľubor; Jeong, SoHyeon; Pollefeys, Marc (ACM Transactions on Graphics (TOG) TOG, 2018)
Many geometric quantities can be computed efficiently for convex meshes. For general meshes, methods for approximate convex decomposition have been developed that decompose a static, non-convex object into a small set of approximately convex parts. The convex hulls of those parts can then be used as a piecewise convex approximation to the original mesh. While previous work was only concerned with static meshes, we present a method for decomposing animated 3D meshes into temporally coherent approximately convex parts. Given a mesh and several training frames—that is, different spatial configurations of its vertices—we precompute an approximate convex decomposition that is independent of any specific frame. Such a decomposition can be transferred in real-time to novel, unseen frames. We apply our method to a variety of pre-animated meshes as well as a 3D character interactively controlled by a user's body pose. We further demonstrate that our method enables real-time physics simulations to interact with animated meshes.
International Conference on Computer Graphics and Interactive Techniques (SIGGRAPH 2018)